Investigation of Quantity, Quality and Energy Content of Indigenous Sugarcane Trash in Naoshehro Feroze District, Sindh - Solangi, S. H.; Jakhrani, A. Q.; Mukwana, K. C.; Jatoi, A. R.; Luhur, M. R. (Engineering, Technology & Applied Science Research, 2018)
Quantity, characteristics, and energy content in sugarcane trash of six different indigenous sugarcane varieties were computed for their possible utilization. Results revealed that the total sugarcane trash weight percentage was 24.0% of the total sugarcane crop. Among all examined varieties, variety 240 produced the highest and the variety HS12 the lowest percentage of sugarcane trash with 28% and 18.6% respectively. Moisture and ash content were found less in brown leaves and more in the tops of sugarcane trash parts. The fixed carbon values in brown leaves, green leaves, and tops of the variety Thatta10 were the highest found, with 18.4%, 15.5%, and 17.3% respectively. Carbon element’s percentage in brown leaves of variety HS12 was the highest with 50.0% and in Thatta10 was the lowest with 43.4%. Highest heating value was found in Thatta10 with 16.0MJ/kg, which is close to the literature reported values.